Жіночі образи у творах Марусі Вольвачівни, Марії Проскурівни та Тетяни Сулими - Брижіцька, І. (Літературознавчі обрії. Праці молодих учених, 2010)
The article is devoted to the problem of women characters in the writings by Marusya Volvachivna, Maria Proskurivna and T tyana Sulyma. The author presented a classification of women characters in the texts studied and gave a general comparative analysis of them.